2018
DOI: 10.1186/s40478-018-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes impairs odour detection, olfactory memory and olfactory neuroplasticity; effects partly reversed by the DPP-4 inhibitor Linagliptin

Abstract: Recent data suggest that olfactory deficits could represent an early marker and a pathogenic mechanism at the basis of cognitive decline in type 2 diabetes (T2D). However, research is needed to further characterize olfactory deficits in diabetes, their relation to cognitive decline and underlying mechanisms.The aim of this study was to determine whether T2D impairs odour detection, olfactory memory as well as neuroplasticity in two major brain areas responsible for olfaction and odour coding: the main olfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 92 publications
1
36
0
Order By: Relevance
“…However, previous studies in GK rats only revealed deficits at later times, including deficits in novel object recognition observed at 24 weeks of age, 48 deficits in memory retention observed at 10 weeks, 49 and deficits in olfactory memory at 6 to 10 months. 35…”
Section: Discussion Retinal Changes Appear Prior To Cognitive and Motmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies in GK rats only revealed deficits at later times, including deficits in novel object recognition observed at 24 weeks of age, 48 deficits in memory retention observed at 10 weeks, 49 and deficits in olfactory memory at 6 to 10 months. 35…”
Section: Discussion Retinal Changes Appear Prior To Cognitive and Motmentioning
confidence: 99%
“…The GK rat is a non-insulin-dependent, polygenic, nonobese model that develops impaired glucose-induced Copyright 2019 The Authors iovs.arvojournals.org j ISSN: 1552-5783 insulin secretion by 2 weeks and fasting hyperglycemia by 4 weeks. 30,31 Retinal 32,33 and cognitive deficits [34][35][36] and reduced motor nerve conduction 37 have been reported in the GK rat. However, the temporal appearance of these deficits and the relationship between them has not been described.…”
mentioning
confidence: 98%
“…Olfactory memory is affected in Alzheimer's disease [16]. Lietzau et al showed that type 2 diabetes may impair olfactory memory and odor detection and decreases neurogenesis in the olfactory bulb [17]. Several hypotheses have been made to try to explain the olfactory dysfunction in diabetes, including the possibility that endocrine and vascular changes may lead to neuropathy and damage to the olfactory nerve [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A population‐based study showed patients using pioglitazone as an antidiabetic drug are at lower risk of developing dementia when compared with other drugs used to treat the same (Lu, Yang, Li, Hsieh, & Ou, ; Thabit & El, ). Also, DPP‐4 inhibitors like linagliptin and vildagliptin showed reduced memory impairment when used as a treatment approach in rats (Lietzau et al, ; Zhang et al, ). Moreover, probucol showed a decline in cognitive impairment in an insulin resistant mouse by protecting its blood–brain barrier (Mamo et al, ).…”
Section: Curing Diabetes Associated Alzheimer's Disease: a Long Way Tmentioning
confidence: 99%
“…inhibitors like linagliptin and vildagliptin showed reduced memory impairment when used as a treatment approach in rats (Lietzau et al, 2018;Zhang et al, 2018). Moreover, probucol showed a decline in cognitive impairment in an insulin resistant mouse by protecting its bloodbrain barrier (Mamo et al, 2018).…”
Section: Insulinmentioning
confidence: 99%